Translation techniques of Malay audiovisual translation in The Spiderwick Chronicles movie - Norsham, Nurul Izzah Syamimi Syahirah; Mohd Basari, Shahrul Nizam (Kulliyyah of Sustainable Tourism and Contemporary Languages, 2024)
This study investigated the types of translation techniques in the audiovisual translation (AVT) of The Spiderwick Chronicles movie and the most used techniques in the movie. Using Molina and Albir’s translation theory, this research used a qualitative approach employing a content analysis to analyse the data. The findings revealed that there were 16 out of 18 Molina and Albir’s translation techniques applied in the AVT of the movie, while the most used types of translation techniques are literal translation technique, followed by reduction technique and linguistic compression technique. To conclude, the translation techniques in the AVT of The Spiderwick Chronicles helped the audience to understand the movie despite the language barrier.